(untitled) (Perner’s Contacts, 2010)
This paper deals with change of selected indicators of disabled passengers (wheelchairs) transportation in urban transport system. Change of circulation speed, number of vehicles on line and time interval on line are there under different intensity of wheelchairs transportation, different long of line and other aspects calculate.